Reaction Mechanism and Kinetic Model of the Transformation of Iron Monosulfides Thin Films into Pyrite Films. - Morales Sánchez, Carlos; Pascual, Antonio; Leinen, Dietmar; Luna López, Gabriel; Ares Fernández, José Ramón; Flege, Jan Ingo; Soriano de Arpe, Leonardo; Jiménez Ferrer, Isabel; Sánchez López, Carlos (American Chemical Society, 2025)
This work presents a comprehensive reaction and kinetic model of the pyrite thin films formation by sulfuration of Fe monosulfides when a molecular sulfur (S2) atmosphere is used. This investigation completes the results already published on the explanation and interpretation of the sulfuration process that transforms metallic iron into pyrite. It was previously shown that the monosulfide species (i.e., orthorhombic and hexagonal pyrrhotite phases) are intermediate phases in the sulfuration reaction. Based on experimental data we now show that the sulfuration of pyrrhotite to pyrite takes place in two distinct stages: (i) conversion of orthorhombic pyrrhotite to pyrite (Fe1–xSO → FeS2) while the hexagonal pyrrhotite (Fe1–xSH) phase remains unaltered, and (ii) final transformation of hexagonal pyrrhotite to pyrite (Fe1–xSH → FeS2). Both processes occur via interstitial sulfur diffusion through the previously formed pyrrhotite layer. Consequently, the monosulfide is sulfurated at the internal Fe1–xS/FeS2 interface. The reaction mechanism at each stage has been validated using the corresponding kinetic model to fit the experimental data on time evolution of Fe1–xS and FeS2 layers thicknesses and some of the film transport properties. The concluding global reaction mechanism proposed in some of our former papers and completed here (Fe → Fe1–xS → FeS2) can explain the resulting microstructure of the pyrite films (i.e., Kirkendall effect and formation of a porous layer in the film). Simultaneously, it also justifies the presence of intrinsic defects, such as iron and sulfur vacancies, and the accumulation of interstitial sulfur at the film grain boundaries. The conductivity of pyrite films is tentatively explained using a two-band model where the changes in the Seebeck coefficient and the S/Fe ratio during the pyrite recrystallization stage can be successfully explained.
Keywords: Piritas - Aspectos moleculares; Sulfuración; Diffusion; Pyrite; Sulfur; Thickness; Thin Films